Are genetic variations in IL-1β and IL-6 cytokines associated with the risk of pre-eclampsia? Evidence from a systematic review and meta-analysis. (12th December 2022) - Nasri, Fatemeh; Zare, Maryam; Hesampour, Fatemeh; Ahmadi, Moslem; Ali-Hassanzadeh, Mohammad; Mostafaei, Shayan; Gharesi-Fard, Behrouz
Abstract: Objective: This systematic review and meta-analysis study was performed to assess the potential association between interleukin-1 beta (IL-1β) single nucleotide polymorphisms (SNPs) (rs1143634 and rs16944) and interleukin-6 (IL-6) SNP (rs1800795) and pre-eclampsia (PE). Methods: A comprehensive literature search was conducted in the international search engines and databases, including MEDLINE (via PubMed), Scopus, and Web of Science (ISI) up to 9 March 2021. After retrieving relevant articles, data extraction was performed by four authors independently. Pooled ORs and corresponding 95% CIs were used to evaluate the association between IL-1β and IL-6 polymorphisms and PE risk. Cochran's Q test was used to check heterogeneity, and the I 2 index was calculated for measuring the heterogeneity between the estimations of included studies. Results: After reviewing fully published studies, 21 studies were included in this study based on the eligibility criteria. Our results showed that rs16944 and rs1143634 of IL-1β were significantly associated with the risk of PE. Regarding rs16944, the minor C allele significantly decreased the risk of PE (C vs. T: OR = 0.79, 95% CI = 0.69–0.90). In contrast, the minor T allele of rs1143634 significantly increased the risk of PE (T vs. C: OR = 1. 28, 95% CI = 1.04–1.58). There was no significant association between IL-6 rs1800795 (C vs. G: OR = 1.04, 95% CI = 0.93–1.16) polymorphism and PE risk. Conclusions: In conclusion, this meta-analysis suggests rs1143634 and rs16944 polymorphisms of IL-1β are related to the risk of PE.